The Main Themes, Motifs and Images Of A.Feinberg's Lyrics - Kuldashevna, Yuldasheva Lola (Jurnal Pendidikan Non formal, 2024)
Alexander Arkadyevich Feinberg is one of the first Russian-speaking national poet of Uzbekistan. The work of Alexander Feinberg continued the best traditions of classical poetry, and contributed to the widespread spread of the Russian language and literature, culture in our country. In this article highlights of the main themes, motifs and images of A.Feinberg's lyrics and its importance in youth artistic notions.